Automatic Attendance Recording Using Face Recognition - Pandey, Anjana; Gupta, Kanika; Agrawal, Shivang (International Journal of Computer Sciences and Engineering, 2019)
Face Recognition is an application in the computer vision industry .Many algorithms has been developed in order to achieve facial recognition with most accuracy. Face recognition is less sturdy than other biometric scanning systems like fingerprint and retina scanning. This report describes the face detection and recognition minor-project developed for the attendance system of the department where a student can view his attendance on the dates present and teacher can check the attendance and save it in pdf format. This project uses the technologies available in the OpenComputerVision (OpenCV) library in java interface and methods to implement them using . This project is accomplished using Haar-Cascades for face detection and Local binary pattern histograms(LBPH) for face recognition. The process is represented together with flow charts for every stage of the system. Next, the results are shown using screen-shots.